2020
DOI: 10.1186/s13045-020-00947-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeting immune checkpoints in hematological malignancies

Abstract: Immune checkpoint blockade (ICB) therapies such as anti-programmed death 1 (PD-1) and anti-CTLA-4 (cytotoxic T lymphocyte-associated protein 4) have dramatically transformed treatment in solid tumor oncology. While immunotherapeutic approaches such as stem cell transplantation and anti-cancer monoclonal antibodies have made critical contributions to improve outcomes in hematological malignancies, clinical benefits of ICB are observed in only limited tumor types that are particularly characterized by a high inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 186 publications
0
85
0
Order By: Relevance
“…4 e and Supplementary Figure 4 B). Immunotherapies have changed the methods of cancer treatment subversively, such as the application of checkpoint inhibitors targeting PD-1 and CTLA-4 [ 74 , 75 ]. But these strategies are not always efficacious, which is partly due to the difference of heterogeneity and/or ability of tumor-infiltrating T lymphocytes.…”
Section: Resultsmentioning
confidence: 99%
“…4 e and Supplementary Figure 4 B). Immunotherapies have changed the methods of cancer treatment subversively, such as the application of checkpoint inhibitors targeting PD-1 and CTLA-4 [ 74 , 75 ]. But these strategies are not always efficacious, which is partly due to the difference of heterogeneity and/or ability of tumor-infiltrating T lymphocytes.…”
Section: Resultsmentioning
confidence: 99%
“…A series of clinical studies showed that anti-PD-1/ PD-L1 antibodies had robust and durable anti-cancer activities across several solid and hematologic cancers, such as lung cancer [7][8][9], renal cell cancer [10], melanoma [11], hepatocellular carcinoma [12], as well as lymphoma [13][14][15]. Besides, synergistic anti-tumor responses have been observed in combination of anti-PD1/PD-L1 with PARP inhibition [16] or radiotherapy [17].…”
Section: Introductionmentioning
confidence: 99%
“…With the emergence of immune checkpoint blockade (ICB) therapy, immune checkpoint inhibitors have considerably transformed clinical decision-making in cancer oncology [ 38 40 ]. Subsequently, six key immune checkpoint inhibitors genes (PDCD1, CD274, PDCD1LG2, CTLA‐4, HAVCR2, and IDO1) [ 34 36 ] were correlated.…”
Section: Resultsmentioning
confidence: 99%